2021
DOI: 10.1002/adsu.202100022
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of the Low Temperature Carbonation Kinetics of Calcium Oxide for Potential Thermochemical Energy Storage Purposes and Sustainable CO2 Fixation

Abstract: The pressure effect on the carbonation behavior of CaO as model compound is studied under mild hydrothermal conditions, as relevant to sustainable geological CO2 sequestration and for potential utilization in thermochemical energy storage. Reaction yields are determined experimentally by means of in situ powder X‐ray diffraction using CaO powder samples in a controlled reaction with CO2 under gas pressures between 1.0 and 5.0 MPa and at temperatures between 298 and 373 K. The results show a two‐step conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Thus, the rate-limiting step of the overall reaction mechanism is the diffusion process of H 2 O and CO 2 . This is typical for two-step consecutive reactions and has been investigated for calcium oxide in detail , as well as for other compounds, such as calcium silicate . For LLZO, such detailed kinetic studies of both hydration and carbonation have not been reported before.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the rate-limiting step of the overall reaction mechanism is the diffusion process of H 2 O and CO 2 . This is typical for two-step consecutive reactions and has been investigated for calcium oxide in detail , as well as for other compounds, such as calcium silicate . For LLZO, such detailed kinetic studies of both hydration and carbonation have not been reported before.…”
Section: Resultsmentioning
confidence: 99%
“…There are various complex mathematical models considering material properties, e.g., porosity, molar flux, diffusivity of gas educts, and changes of particle size during the reaction. Details including the required assumptions can be found in elsewhere. …”
Section: Resultsmentioning
confidence: 99%
“…Carbonate Formation Mg 2+ + CO 3 2− → MgCO 3(s) Ca 2+ + CO 3 2− → CaCO 3(s) Despite the simplicity of the stoichiometric reactions describing the formation of Ca- or Mg-carbonates, complex chemo-morphological interactions result in non-monotonic kinetics of carbonate nucleation and growth. For example, the kinetics of carbon mineralization are strongly influenced by the pH and composition of the aqueous phase, 51 partial pressure of CO 2 , 52 and temperature. 34 pH conditions greater than 8 favor (bi)carbonate formation which aid in solid carbonate formation while more acidic pH conditions favor the dissolution of Ca- or Mg-oxides and hydroxides.…”
Section: Resultsmentioning
confidence: 99%
“…Hangx et al [ 23 ], found that the integrity of the caprock is dependent on the stress-strain changes that are exposed to the rock. According to Aminu et al [ 26 ], and Gravogl et al [ 35 ], the viable candidate technology for carbon dioxide subsurface storage should provide a minimum residence length of 1000 years and a leakage rate of less than 0.1 % annually. Injection and storage of carbon dioxide may drastically influence the geo-mechanical and geochemical characteristics of caprocks.…”
Section: Introductionmentioning
confidence: 99%